PENGEMBANGAN BUKU SAKU HAFALAN NIAT DAN BACAAN SHALAT SEBAGAI MEDIA PEMBELAJARAN PRAKTIS BAGI SISWA KELAS X DI SMK NEGERI 1 BELITANG MADANG RAYA - Septina, Bella; Sodikin, Ahmad; Suhartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education learning, particularly on prayer intentions and recitations, still faces challenges due to the limited availability of practical learning media and students’ low ability to memorize prayer recitations independently. This study aimed to develop a Pocket Book of Prayer Intentions and Recitations, determine its validity, and assess its practicality for tenth-grade students at SMK Negeri 1 Belitang Madang Raya. This research employed the Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The validity test involved a material expert and a media expert, while the practicality test involved 36 tenth-grade accounting students and an Islamic Religious Education teacher. The results showed that the product achieved a validity score of 94% categorized as very valid and a practicality score of 84.24% categorized as very practical. Therefore, the Pocket Book of Prayer Intentions and Recitations is feasible to be used as a supporting learning medium in Islamic Religious Education.